Management of Acute Diarrhea in Community Pharmacists in Sana’a City, Yemen - Al-Akhali, Khaled; Mahyuob, Abdullah (Journal of Pharmacy Practice and Community Medicine)
Background: Community pharmacists play a critical role in the management of acute diarrhea, especially in low-resource settings. However, evidence suggests that their counseling, medication-labeling, and dispensing practices particularly antibiotic use may not always align with best practice standards. Aim: To assess management of acute diarrhea in community pharmacists in Sana’a city, Yemen. Materials and Methods: A cross-sectional survey was conducted among 349 community pharmacy professionals in Sana’a city between December 2022 and January 2023. The questionnaire addressed demographic characteristics, type of pharmacy, and a 10 key practice items covering counseling content, labeling, patient history, explanation of therapy benefits/risks, and whether they dispense antibiotics for gastroenteritis. Results: Among 349 respondents, 99.14% were male. Independent pharmacies accounted for 57.31% of workplaces, and chain pharmacies 42.69%. Regarding practice; 76.5% wrote the medicine name on dispensed medicines, 71.6% included drug strength, and 55.6% informed patients about expiry dates. For counseling; 84.8% explained medicine name/indication/dosage/ route; 84.2% explained dose, frequency and course duration; 72.2% explained time to effect; 82.8% discussed therapy duration. Only 69.9% asked about allergies or concurrent treatments; 71.4% discussed benefits/risks; and 64.2% reported dispensing antibiotics for gastroenteritis. Conclusion: The findings reveal that while a majority of community pharmacists in Sana’a report providing essential counseling and labeling information, substantial deficiencies remain particularly in allergy history taking, expiry-date communication, and widespread dispensing of antibiotics for acute diarrhea. These patterns raise concerns about patient safety and rational drug use.
Keywords: Acute Diarrhea; Antibiotic Dispensing; Community Pharmacy; Counseling Practices; Yemen